2008
DOI: 10.1371/journal.pone.0001627
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Catarrhal Fever Induced by Alcelaphine herpesvirus 1 Is Associated with Proliferation of CD8+ T Cells Supporting a Latent Infection

Abstract: Alcelaphine herpesvirus 1 (AlHV-1), carried by wildebeest asymptomatically, causes malignant catarrhal fever (WD-MCF) when cross-species transmitted to a variety of susceptible species of the Artiodactyla order. Experimentally, WD-MCF can be induced in rabbits. The lesions observed are very similar to those described in natural host species. Here, we used the rabbit model and in vivo 5-Bromo-2′-Deoxyuridine (BrdU) incorporation to study WD-MCF pathogenesis. The results obtained can be summarized as follows. (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
59
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 44 publications
7
59
3
Order By: Relevance
“…Phenotyping of mononuclear leukocytes infiltrating lymphoid and nonlymphoid tissues during WD-MCF. We previously observed that WD-MCF is associated with proliferation of CD8 ϩ T cells that become the predominant cell type in lymphoid tissues with the progression of the disease (12). Here, we phenotyped the mononuclear leukocytes infiltrating lymphoid and nonlymphoid tissues during WD-MCF.…”
Section: Vol 85 2011 Ex Vivo Imaging Of Malignant Catarrhal Fever 6947mentioning
confidence: 96%
See 4 more Smart Citations
“…Phenotyping of mononuclear leukocytes infiltrating lymphoid and nonlymphoid tissues during WD-MCF. We previously observed that WD-MCF is associated with proliferation of CD8 ϩ T cells that become the predominant cell type in lymphoid tissues with the progression of the disease (12). Here, we phenotyped the mononuclear leukocytes infiltrating lymphoid and nonlymphoid tissues during WD-MCF.…”
Section: Vol 85 2011 Ex Vivo Imaging Of Malignant Catarrhal Fever 6947mentioning
confidence: 96%
“…Total DNA was extracted from PBMC or pLN cells using the QIAamp miniprep kit (Qiagen). AlHV-1 genomic DNA copies were quantified using an AlHV-1 ORF3 real-time PCR with normalization on the cellular beta-globin genomic sequence, as described previously (12). Viral and cellular gene-specific primers are listed in Table 1.…”
Section: Vol 85 2011 Ex Vivo Imaging Of Malignant Catarrhal Fever 6943mentioning
confidence: 99%
See 3 more Smart Citations